2007
DOI: 10.1016/j.jfms.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lysine supplementation in cats with enzootic upper respiratory disease

Abstract: To determine the effectiveness of dietary lysine supplementation in cats with enzootic upper respiratory disease (URD), 50 cats were fed a ration containing 11 or 51 g lysine/kg diet for 52 days. Food intake, body weight, clinical signs, plasma amino acid concentrations and presence of Chlamydophila felis or feline herpesvirus (FHV)-1 DNA within the conjunctival fornix were assessed. Food and lysine intake of both dietary groups decreased between days 17 and 22, coinciding with peak disease and viral presence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 22 publications
2
42
2
1
Order By: Relevance
“…68 ✜ In a larger study, addition of lysine to the diet of 50 cats with enzootic upper respiratory tract disease actually increased the severity of clinical signs and FHV-1 DNA detection rates. 69 ✜ In a large clinical study within an animal shelter (144 treated cats, 147 controls), dietary lysine supplementation did not reduce FHV-1 infection rates in the experimental group compared with the control group. 70 ✜ Another large controlled study involving 261 animal shelter cats reached similar conclusions, with lysine-dosed cats developing more severe clinical signs and higher FHV-1 DNA detection rates than control cats.…”
Section: L-lysinementioning
confidence: 95%
“…68 ✜ In a larger study, addition of lysine to the diet of 50 cats with enzootic upper respiratory tract disease actually increased the severity of clinical signs and FHV-1 DNA detection rates. 69 ✜ In a large clinical study within an animal shelter (144 treated cats, 147 controls), dietary lysine supplementation did not reduce FHV-1 infection rates in the experimental group compared with the control group. 70 ✜ Another large controlled study involving 261 animal shelter cats reached similar conclusions, with lysine-dosed cats developing more severe clinical signs and higher FHV-1 DNA detection rates than control cats.…”
Section: L-lysinementioning
confidence: 95%
“…It may therefore be of use early in acute disease or as a means of reducing the severity of disease and virus shed at times of stress: suggested dosage regimens are described elsewhere [82,128]. There is evidence that dietary lysine supplementation is not effective in groups of cats and that maybe bolus administration is essential [84]. Bovine lactoferrin has shown some in vitro activity most likely by preventing attachment and penetration of FeHV-1 into susceptible cells [2], but in vivo efficacy has not yet been evaluated.…”
Section: Treatmentmentioning
confidence: 99%
“…179 It is optimal when used early in infection, or as a means to prevent recrudescence during stress, where it has been shown to reduce viral shedding in latently infected cats. 183 However, food intake (and therefore lysine intake) decreased when lysine was added to the diet. 243 In fact, one study actually found increased viral shedding and severity of signs of URTD in shelter cats fed lysine supplements.…”
Section: Feline Calicivirusmentioning
confidence: 99%
“…243 In fact, one study actually found increased viral shedding and severity of signs of URTD in shelter cats fed lysine supplements. 183 In one study, plasma arginine concentrations declined in lysine-supplemented cats during a 52-day monitoring period, leading the authors to recommend monitoring of plasma arginine in cats receiving long-term lysine supplementation. 183 However, food intake (and therefore lysine intake) decreased when lysine was added to the diet.…”
Section: Feline Calicivirusmentioning
confidence: 99%
See 1 more Smart Citation